Coordinated effect of PHEVs with DGs on distribution network. (26th December 2018) - Jha, Bablesh Kumar; Kumar, Abhishek; Singh, Devender; Misra, Rakesh Kumar
Summary: In this paper, a base case of distribution system without PHEVs and DGs has been studied to evaluate system performance characteristics. Further, effect of introduction of PHEVs has been investigated in terms of system operating cost, losses, voltage profile, and load flattening. To improve these characteristics, introduction of DGs has been investigated by simulating different penetration level of PHEVs along with different demand response (DR) levels. It has been demonstrated that with the DG scheduling considering appropriate DR levels, the system operating cost, losses, voltage profile, and load flattening can be improved. The 24‐hour DG scheduling is carried out to optimize the system cost, which is function of charging/discharging cost, losses, and cost of DGs power. A differential evolution (DE) search algorithm is used to optimize single objective weighted fitness function. IEEE 38‐Bus test system is used for demonstration of the investigations. In case of lower‐penetration levels, operating cost is significantly affected by the DR characteristics of a system. The method suggested can help local distribution companies (LDC) in optimally scheduling the DGs, in presence of PHEV, to achieve the minimum system cost, improved voltage profile, minimum losses, and improved load fattening.